2014
DOI: 10.1161/circresaha.115.304361
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-195 in Aortic Aneurysmal Disease

Abstract: The ECM is the key structural component determining dilatation and aneurysm formation in the aortic wall. 8 Abdominal aortic aneurysms (AAAs) are characterized by loss of elastin and increased collagen turnover. Apart from miR-29, the miR-15 family has been implicated in collagen remodeling and the characteristic postnatal silencing of elastin.9 The miR-15 family consists of 6 highly conserved microRNAs (miR-15a, miR15b, miR-16-1, miR-16-2, miR-195, and miR-497), which are clustered on 3 separate chromosomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 32 publications
3
100
0
Order By: Relevance
“…OR, odds ratio. including targets that would not have been anticipated based on current bioinformatics prediction models (11,16). To complement our clinical studies, we used a proteomics approach to identify putative protein targets of miR-27b and miR-320a in the secretome of ECs.…”
Section: Proteomics For Mirna Target Identificationmentioning
confidence: 99%
“…OR, odds ratio. including targets that would not have been anticipated based on current bioinformatics prediction models (11,16). To complement our clinical studies, we used a proteomics approach to identify putative protein targets of miR-27b and miR-320a in the secretome of ECs.…”
Section: Proteomics For Mirna Target Identificationmentioning
confidence: 99%
“…The available evidence supports the concept that a link exists between circulating IGF-1 levels and miRNA expression (Bake et al 2014;Bates et al 2010;Fenn et al 2013;Marino et al 2010;Victoria et al 2015). Demonstration of IGF-1-dependent changes in miRNA biology in the vasculature is particularly important (Bonauer et al 2009;Chen et al 2015;Doebele et al n.d.;Hergenreider et al 2012;Kim et al 2014;Kuehbacher et al 2007;Leung et al 2013;Lovren et al 2012;O'Rourke and Olson 2011;Rotllan et al 2013;Stellos and Dimmeler 2014;Weber et al 2014;Zampetaki et al 2014) as changes in miRNA expression have been causally linked to the development of cardiovascular aging phenotypes (Boon et al 2013;Csiszar et al 2014;Ungvari et al 2013) and the pathogenesis of cardiovascular diseases (Ono et al 2011).…”
Section: Discussionmentioning
confidence: 63%
“…There is growing evidence that miRNAs control lifespan and the pace of aging in model organisms (Boehm and Slack 2005;Grillari and GrillariVoglauer n.d.;Ibanez-Ventoso et al 2006) and that changes in miRNA expression profile also have a role in mammalian aging (Bates et al n.d.;Inukai et al 2012;Inukai and Slack 2013;Ito et al 2010;Maes et al 2008;Mercken et al 2013;Smith-Vikos and Slack 2012;Ungvari et al 2013;Zhang et al 2012;Zovoilis et al 2011). Importantly, miRNAs were also reported to regulate several important aspects of endothelial biology and vascular function (Bonauer et al 2009;Chen et al 2015;Doebele et al n.d.;Hergenreider et al 2012;Kim et al 2014;Kuehbacher et al 2007;Leung et al 2013;Lovren et al 2012;O'Rourke and Olson 2011;Rotllan et al 2013;Stellos and Dimmeler 2014;Weber et al 2014;Zampetaki et al 2014). Further, age-related changes in miRNA expression were shown to contribute to the development of cardiovascular aging phenotypes (Boon et al 2013;Csiszar et al 2014;Ungvari et al 2013) and the pathogenesis of cardiovascular diseases (Ono et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some recent studies clearly demonstrated the roles of miRNAs in the development of AAA [41][42][43][44]. Zampetaki et al [45] examined miR-195, a member of the miR-15 family. The authors performed proteomic analysis of the secretome of murine aortic smooth muscle cells, after miR-195 manipulation, confirming that miR-195 regulates numerous ECM elements such collagens (COL1A1, COL1A2, and COL3A1).…”
Section: Resultsmentioning
confidence: 99%